A New Approach of Thin Coated Adsorbent Layer for Batch Adsorption Using Basic Dye - Azha, S. F.; Ahmad, A. L.; Ismail, S. (ASEAN Journal of Chemical Engineering, 2015)
Clay based adsorbent which formulated to acts as thin coated adsorbent layer (TCAL) is a new approach for adsorption of coloured wastewater. In this study, TCAL has been evaluated for the removal of methylene blue dye as an adsorbate from aqueous solution. It was prepared by combination formula of commonly known clay based adsorbent, a binder as well as solvent. This paper focused on evaluation of TCAL in terms of performance including effects of different types of binder used and ratio of adsorbent to binder. The study effect on ratio was targeted for its coating strength, contact time as well as percentage dye removal. The experimental data reported that the water based binder was the most suitable binder to be used in TCAL in terms of adsorption performance and gave strength to the coating adsorbent itself. The optimum ratio of adsorbent to binder is 0.3/2.5 weight mass. The percentage removal test for 100 mg/L concentration of Methylene Blue in batch adsorption of adsorbent coating layer was found to achieve 100 % removal within less than 3 hours. Elemental analysis and morphological structure were also determined. The finding revealed the potential of TCAL as an effective adsorbent for undertaken adsorption process on basic dye.